(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Internal Social Responsibility is the one that is directed to the social aspects of a company’s own activity such as the training of its workers, the proportion of a decent job, work incentives, food supports, among others. Because Social Responsibility is an intangible resource, it should not be downplayed, since it can actually generate improvements in the competitiveness of companies in the sector belonging to human resources and it is important to implement in microenterprises. This article addressed the relationship between Social Responsibility with quality of life and the correct use of human capital through decent employment, competitiveness and significant growth in micro-enterprises because this type of activity is usually related to large companies, however, it is possible to apply it in micro-enterprises. Human resources management serves as an important managerial support in the management of labor relations, the strengthening of the organizational culture and the promotion of a good work environment, thus enhancing the retention of talents and increased productivity. On the methodology that was used in the preparation of this article, a literary review of various articles and books was carried out, in addition to conceptual theoretical analysis. The article is also exploratory, aimed at entrepreneurs, owners of microenterprises, people related to the administration of microenterprises, and all the public interested in this topic.